1999
DOI: 10.1002/(sici)1522-7278(199905)14:2<271::aid-tox8>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of the aquatic oligochaetes Lumbriculus variegatus and Tubifex tubifex for assessing the toxicity of copper and cadmium in a spiked‐artificial‐sediment toxicity test

Abstract: ABSTRACT:A sediment toxicity test using the freshwater oligochaetes Lumbriculus variegatus and Tubifex tubifex was performed. We evaluated acute and chronic toxicity affects of copper and cadmium on reproduction in both species and the bioaccumulation of both metals by L. variegatus using artificial sediment. L. variegatus bioconcentrated copper 22-fold and cadmium 16-fold after a 14-day exposure to spiked artificial sediments with 0.02% organic content. The EC for T. tubifex varied depending upon 50 endpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 12 publications
(18 reference statements)
1
16
1
1
Order By: Relevance
“…This contrasts the findings of Chapman et al (1999), who reported significant mortality of L. variegatus after 14 d of exposure to Cu-spiked sediment at 50 g g −1 . The high sensitivity to Cu observed in L. variegatus by Chapman et al (1999) in comparison to our results may be caused by their use of artificial sediment with the low organic contents (0.02%) and the longer exposure times in the former study.…”
Section: Dietborne Cu Biodynamics and Toxicitycontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts the findings of Chapman et al (1999), who reported significant mortality of L. variegatus after 14 d of exposure to Cu-spiked sediment at 50 g g −1 . The high sensitivity to Cu observed in L. variegatus by Chapman et al (1999) in comparison to our results may be caused by their use of artificial sediment with the low organic contents (0.02%) and the longer exposure times in the former study.…”
Section: Dietborne Cu Biodynamics and Toxicitycontrasting
confidence: 99%
“…This contrasts the findings of Chapman et al (1999), who reported significant mortality of L. variegatus after 14 d of exposure to Cu-spiked sediment at 50 g g −1 . The high sensitivity to Cu observed in L. variegatus by Chapman et al (1999) in comparison to our results may be caused by their use of artificial sediment with the low organic contents (0.02%) and the longer exposure times in the former study. Overall, the observed mortality in the sediment exposures (Table S3) agreed well with the reported lowest observed effect concentration (LOEC, 140 g Cu g −1 dw) as well as the no observed effect concentration (NOEC, 114 g Cu g −1 dw) previously reported for this species (both based on survival after 28 d; Roman et al, 2007).…”
Section: Dietborne Cu Biodynamics and Toxicitymentioning
confidence: 99%
“…According to Brinkhurst (1999), the majority of publications on oligochaetes up to 1970 were taxonomic, containing descriptions of new species and re-descriptions of known ones. In the 31 years examined , studies with ecological focus stood out over the other areas of knowledge, although the number of taxonomic works also continued to rise in the those years.…”
Section: Discussionmentioning
confidence: 99%
“…This work has included metals (e.g. Schubauer-Berigan et al 1993;Chapman et al 1999), metal oxides (e.g. Stanley et al 2010), various chemicals (e.g.…”
Section: Introductionmentioning
confidence: 99%